2014
DOI: 10.1093/jnci/dju403
|View full text |Cite
|
Sign up to set email alerts
|

Induced Phenotype Targeted Therapy: Radiation-Induced Apoptosis-Targeted Chemotherapy

Abstract: Such a phenotype induction strategy represents a conceptually novel approach to overcome tumor heterogeneity and complexity as well as to substantially improve current conventional chemoradiotherapy with fewer sequelae and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…Enhanced apoptosis is one of the key anti-tumor responses mediated by EphB4 targeting and radiation325262728. In caspase-3/7 assay, we observed a significant increase in apoptosis (~28%) in Fadu cells transfected with EphB4-siRNA and 4 Gy dose of radiation compared to radiation alone at 96 h (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Enhanced apoptosis is one of the key anti-tumor responses mediated by EphB4 targeting and radiation325262728. In caspase-3/7 assay, we observed a significant increase in apoptosis (~28%) in Fadu cells transfected with EphB4-siRNA and 4 Gy dose of radiation compared to radiation alone at 96 h (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies have found a correlation between radiation and programmed cell death27284445. Importantly, EphB4 knockdown has been reported to promote cell death by apoptosis339.…”
Section: Discussionmentioning
confidence: 97%
“…Kim and co-workers recently developed an induced phenotype targeted therapy (IPTT) where DEVD-S-DOX prodrug containing DOX linked to a peptide moiety (DEVD) is cleaved by an enzyme caspase-3. Caspase three expression is elevated in tumor region by radiation induced apoptosis [196]. Several enzyme cleavable peptide prodrug conjugates and formulations of DOX have been recently developed to increase the specificity and tolerability of chemotherapeutic agents [197205].…”
Section: Prodrug Approach: Analog / Chemical Conjugation For Cancementioning
confidence: 99%
“…Lee et al described a novel strategy called induced phenotype targeted therapy to simplify targets complicated by tumor heterogeneity and to overcome tumor evolutionary complexity [20]. In this strategy, a specific apoptotic phenotype was artificially induced and used as a target for prodrugs.…”
Section: Magnified Viewmentioning
confidence: 99%